Ecosufism as a Paradigm of Environmental Ethics in Islamic Education - Nur Isra' Ahmad (Mahad Aly Al Fithrah, 2026)
The global ecological crisis, marked by extreme climate change, global warming, pollution, deforestation, and biodiversity loss, highlights that environmental problems are not merely technical but also carry ethical and spiritual dimensions. In the Indonesian educational context, many schools have yet to establish a sustainable ecological culture, making environmental education largely ceremonial and less effective in fostering ecological awareness among students. This study aims to formulate the paradigm of ecosufism as an Islamic educational approach that integrates Sufi values with ecological consciousness. The research method employed is library research, analyzing relevant scientific literature published between 2016 and 2026. The findings indicate that ecosufism represents an Islamic educational paradigm that unites Sufi principles with ecological awareness, thereby producing ecological spirituality rooted in Islamic teachings. The internalization of values such as tauḥīd, amanah, tazkiyatun nafs, zuhud, tafakur, iḥsān, sabr, and shukr fosters ecospiritual individuals who are responsible for environmental preservation as part of worship. Within the curriculum, this internalization is realized through the integration of ecological issues into Islamic Religious Education subjects, daily environmentally friendly practices, teacher role modeling, and routine environmental programs. The conclusion emphasizes that Islamic education should not be limited to normative knowledge transfer but must cultivate a sustainable school culture that instills ecological awareness as part of humanity’s role as khalifah on earth. The implication of this study is that ecosufism can serve as a strategic approach in national education policy and provide a foundation for future empirical research to test its effectiveness in enhancing students’ ecological awareness.